Realtime and Liquid Tank Volume Monitoring Based on Internet of Things - Andrizal; Kurniadi, Dedi; Alfitri, Nadia; Humaira; Hafsyah, Fiona Novia (Politeknik Negeri Padang, 2024)
An underground tank is a type of tank installed by burying it on the ground. Underground tanks in the form of a storage area with large dimensions for either liquid or gas, especially BBM (fuel) which is stored underground at Public Fuel Filling Stations his (SPBU). The supply of liquid in this tank really needs to be maintained to meet the need for liquid. In order to be able to monitor the volume of liquid in the underground tank, a device was designed that can monitor the volume of liquid in the tank remotely. This device uses an ultrasonic sensor that can detect the volume of liquid that has been converted from the distance detected by the sensor, and uses Wemos D1 mini on the device and ESP32 on the server as a microcontroller that sends data from the reading process to smartphones and websites. The device works on ultrasonic sensor which can sense the distance and with some calculation it detects how much liquid is sensed as a volume and employs a Wemos D1 mini on the side of device and an ESP32 on the server part as a microcontroller that sends reading data to smartphones and websites. The smartphone displays show liquid volume and distance shown by the sensor while in the server display distance is plotted against time in graphical form. Test results reveal that this device can remotely detect underground tank liquid volume using smartphones or websites with a success rate of 72.35%. This failure rate of 27.65% is caused by curved tanksurface and misplacement of the tank.